The Implementation of Foreign Language Learning Policies at State Islamic Higher Education - Dian Dian (Jurnal Pendidikan Islam, 2019)
Taking a part in foreign language learning in Indonesia has been an effort for the Indonesian people to be able to absorb and keep up with the development of science and meet the demand of global challenge. This study aims to investigate the implementation of foreign language learning policy at one of the state Islamic higher education as well as the challenges it encounters. The method used is descriptive qualitative by using instruments of observation, interviews, and document analysis. The results of this study show that the university implements language learning through the SKS program in regular classes, through courses in the language center, learning in the fields of Ma’had Lughawy and Ma'had Aly (Campus dormitory). Meanwhile, the problems faced in the implementation process are related to human resources, facilities, and learning methods used.